Glass-Ceiling in a Single Mothers Life - Jatiningsih, Oksiana; Sarmini, Sarmini; Habibah, Siti Maizul (The Journal of Society and Media, 2020)
Single mothers face problems not only because of their own status so they have to struggle hard to meet their needs, but also because of patriarchal social construction that presents many challenges to women. This qualitative research is aimed at revealing: the form of glass-ceiling for single mother and their strategies taken to deal with that. This research was conducted in Sidoarjo on five single mothers. Data were collected using in-depth interviews. The theory used is symbolic interaction because it allows researchers to identify research subjects. The results of this study reveal that the glass-ceiling faced by women are domestic responsibilities, sosial control, and underestimation of women. Strategies for dealing with it are sharing work and ignorant of negative responses. The response to the glass-ceiling depends very much on the way of thinking (mind) of women in seeing themselves. When women put themselves away as objects (me) that are powerless against the values that apply, then the choice of action to face the challenges of their lives (glass-ceiling) tends to be compromising and accommodating, whereas if the means adopted are based more on how to see themselves as subjects (I), then the method adopted tends to be uncompromising.